2022
DOI: 10.3390/biomedicines10010113
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Druggable Genes for Asthma by Integrated Genomic Network Analysis

Abstract: Asthma is a common and heterogeneous disease characterized by chronic airway inflammation. Currently, the two main types of asthma medicines are inhaled corticosteroids and long-acting β2-adrenoceptor agonists (LABAs). In addition, biological drugs provide another therapeutic option, especially for patients with severe asthma. However, these drugs were less effective in preventing severe asthma exacerbation, and other drug options are still limited. Herein, we extracted asthma-associated single nucleotide poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…A GWAS is a comprehensive analysis of all genetic variations in the form of SNPs that can be associated with certain traits. GWAS can help detect genetic biomarkers associated with common, complex diseases or phenotypes [ 20 , 31 , 32 , 33 , 34 , 35 ]. An integrated bioinformatics analysis was performed in this study based on candidate genes identified from GWAS loci, GO enrichment analyses, KEGG pathway enrichment analyses, and a constructed PPI network.…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS is a comprehensive analysis of all genetic variations in the form of SNPs that can be associated with certain traits. GWAS can help detect genetic biomarkers associated with common, complex diseases or phenotypes [ 20 , 31 , 32 , 33 , 34 , 35 ]. An integrated bioinformatics analysis was performed in this study based on candidate genes identified from GWAS loci, GO enrichment analyses, KEGG pathway enrichment analyses, and a constructed PPI network.…”
Section: Discussionmentioning
confidence: 99%
“…The selection criteria were adopted from those of Okada Y et al, which were later prioritized for the drug repurposing for rheumatoid arthritis [ 16 ]. These annotations have also been applied for the repurposing of drugs for several other diseases, including chronic hepatitis B [ 17 ], atopic dermatitis [ 18 ], asthma [ 19 ], and colorectal cancer [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, African and American populations were possibly linked more to TNFAIP3 and IRF5 expressions and consequently to higher susceptibility to Sjogren's syndrome. Genomic variants are not only important for the identification of susceptibility of the disease but also it can be used to drive drug discovery (Adikusuma et al, 2021(Adikusuma et al, , 2022Irham et al, 2020Irham et al, , 2022.…”
Section: The Allele Frequencies Of the Candidate Variants In Differen...mentioning
confidence: 99%